Terapi Akupresur Laser untuk Mengatasi Mual Muntah Akibat Kemoterapi pada Pasien Kanker di Ruang Kemoterapi - Sri Endah Handayani; Riri Maria; Sri Yona (Jurnal Keperawatan Silampari, 2022)
This study aims to determine the effect of laser acupuncture in overcoming nausea and vomiting due to chemotherapy in cancer patients. This research method is a literature review through the database Science Direct and Proquest, in the last five years, from 2015 to 2020. The results obtained in each article focus on oncology nurses' roles. In this context, oncology nurses have an essential role in relieving some of the symptoms of cancer, such as using different techniques to improve patients' quality of life and improve various treatment options to support recovery and health care for patients regarding treatment and rehabilitation. In conclusion, laser acupuncture is very safe and effective in reducing nausea and vomiting in cancer patients receiving chemotherapy treatment. Keywords: Chemotherapy, Laser Acupuncture, Nausea, Vomiting